Trawler Engine Size Had No Effect on Baltic Herring Size/Age Structure: An Experimental Study in the Gulf of Riga, Baltic Sea - Elor Sepp; Markus Vetemaa; Tiit Raid; Timo Arula (Fishes, 2022)
The Gulf of Riga stock of Baltic herring (Clupea harengus membras L.) has been maintained through several management tools. One such tool is the restriction of vessels’ main engine power (

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Fishing impact and environmental status in E uropean seas: a diagnosis from stock assessments and ecosystem indicators - Didier Gascuel; Marta Coll; Clive Fox; Sylvie Guénette; Jérome Guitton; Andrew Kenny; Leyla Knittweis; J Rasmus Nielsen; Gerjan Piet; Tiit Raid; Morgane Travers‐Trolet; Samuel Shephard (Fish and Fisheries, 2016)
Stock‐based and ecosystem‐based indicators are used to provide a new diagnosis of the fishing impact and environmental status of E uropean seas. In the seven European marine ecosystems covering the B altic and the N orth‐east A tlantic, (i) trends in landings since 1950 were examined; (ii) syntheses of the status and trends in fish stocks were consolidated at the ecosystem level; and (iii) trends in ecosystem indicators based on landings and surveys were analysed. We show that yields began to decrease everywhere (except in the B altic) from the mid‐1970s, as a result of the over‐exploitation of some major stocks. Fishermen adapted by increasing fishing effort and exploiting a wider part of the ecosystems. This was insufficient to compensate for the decrease in abundance of many stocks, and total landings have halved over the last 30 years. The highest fishing impact took place in the late 1990s, with a clear decrease in stock‐based and ecosystem indicators. In particular, trophic‐based indicators exhibited a continuous decreasing trend in almost all ecosystems. Over the past decade, a decrease in fishing pressure has been observed, the mean fishing mortality rate of assessed stocks being almost halved in all the considered ecosystems, but no clear recovery in the biomass and ecosystem indicators is yet apparent. In addition, the mean recruitment index was shown to decrease by around 50% in all ecosystems (except the B altic). We conclude that building this kind of diagnosis is a key step on the path to implementing an ecosystem approach to fisheries management.

Towards better Understanding of Successful Management of the Gulf of Riga Herring Stock - Tiit Raid; Olavi Kaljuste (Hydrobiologia, 2006)

Factors controlling long-term changes of the eutrophicated ecosystem of Pärnu Bay, Gulf of Riga - Jonne Kotta; Mart Simm; Ilmar Kotta; Inga Kanošina; Kalle Kallaste; Tiit Raid (Hydrobiologia, 2004)